Analisis Studi Kelayakan Bisnis Ghicat’s untuk Usaha Perlengkapan Tempat Tidur Hewan Peliharaan Kucing - Fithriyah, Rd. Ghina; Ramdhani, Muhammad Raihan; Pauji, Achmad Mansur; Perwito, Perwito (Universitas Serambi Mekkah, 2024)
This study discusses Ghicat’s business, a startup focused on providing comfortable and aesthetically pleasing bedding products for pet cats. The growth of the pet industry in Indonesia, especially during the COVID-19 pandemic, has increased the demand for animal care products, including specialized beds. Data shows that 47% of households own a cat, which would suggest a significant market opportunity. This research evaluates various important aspects that contribute to Ghicat’s success, including management, human resources, marketing, finance, and operating technology. Ghicat’s aims to differentiate itself through unique product designs, multifunctional offerings, and a strong online presence on platforms such as Shopee and TikTok Shop. The study also discusses the competitive challenges of local and imported products, emphasizing effective marketing strategies to build consumer trust. Finally, this analysis provides strategic recommendations to ensure Ghicat's sustainability and growth in a competitive market.